PENGUATAN PERAN PEMERINTAHAN MELALUI COLLABORATIVE GOVERNANCE DALAM MENYEDIAKAN LAPANGAN KERJA INKLUSI DI KABUPATEN PASURUAN - Dian Feradiah; Agus Prianto (Journal Publicuho, 2024)
This study aims to strengthen the role of government through collaborative governance in providing inclusive employment in Pasuruan Regency. This research uses descriptive qualitative research methods, data analysis using the interactive model of Miles and Huberman (2014), and aims to describe and analyse 1). Institutional conditions are an effort to fulfil employment opportunities by providing inclusive employment for people with disabilities in Pasuruan Regency; 2). Supporting and inhibiting factors in efforts to fulfil employment opportunities for people with disabilities. The result of this research is that the implementation practice needs to involve collaboration from various stakeholders such as the government, the community, and the private sector. In addition, it requires good institutional quality such as adequate resources, a strong level of trust and networking to ensure accountability from each actor. One of the efforts that can be made to create participatory institutions is through a collaborative governance approach. This model is important to apply in institutional strengthening to overcome weak networks, systems, and levels of trust among stakeholders so that it is expected to be able to create an inclusive environment for disabilities in terms of employment opportunities.